2018
DOI: 10.1080/01480545.2018.1465948
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory role of rutin on 2,5-hexanedione-induced chromosomal and DNA damage in rats: validation of computational predictions

Abstract: The aim of this study was to evaluate the potentials of rutin on 2,5-hexanedione-induced toxicities. Two successive phases were involved using in silico and in vivo approaches. The in silico was adopted for potential oral toxicity and docking. The in vivo was carried-out in two stages for two weeks; the ameliorative (stage 1, first week), preventive, and curative studies (stage 2, extended to second week). In stage 1, rats were divided into four groups of seven each (distilled water, 3% (v/v) 2,5-hexanedione, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Changes in the functional chemistry may as well be connected with membrane stabilizing effects of rutin currently observed bearing in mind that, erythrocytes akin to other cells composed of lipids, proteins and carbohydrates at membranous and non-membranous levels. Rutin has also been reported to have high bioavailability that enhances its antioxidant properties as currently observed based on the decreased in lipid peroxidation and increased in GSH, CAT and SOD (Muhammad et al., 2018). Equally, treatment with rutin has been reportedly associated with anti-inflammatory and protein stability effects which may be beneficial in battling SCD associated oxidative stress, inflammation and decreased haemoglobin S stability (Nafees et al., 2015).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Changes in the functional chemistry may as well be connected with membrane stabilizing effects of rutin currently observed bearing in mind that, erythrocytes akin to other cells composed of lipids, proteins and carbohydrates at membranous and non-membranous levels. Rutin has also been reported to have high bioavailability that enhances its antioxidant properties as currently observed based on the decreased in lipid peroxidation and increased in GSH, CAT and SOD (Muhammad et al., 2018). Equally, treatment with rutin has been reportedly associated with anti-inflammatory and protein stability effects which may be beneficial in battling SCD associated oxidative stress, inflammation and decreased haemoglobin S stability (Nafees et al., 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Arguably, the sickling process in SCD patients is characterized by unceasing polymerization of erythrocytes due to oxidative stress in addition to insufficient oxygen supply distinctive of sickle erythrocytes (Erukainure et al., 2017; Imaga, 2013; Poillon et al., 1995). The antioxidant properties of rutin can help defend against oxidative stress that further enhances the stability of erythrocyte membranes (Muhammad et al., 2018, 2015; Nafees et al., 2015). This come to an agreement with previous studies which showed that treatment with rutin frustrated oxidative stress levels in treated experiments relative to non-treated controls (Muhammad et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proteins groundwork and energy minimization were done with the aid of Discovery studio 2.5v. The CHARMm-based DOCKER program was used to score the interaction between the proteins and the ligand (quercetin) into the crystal structure of the receptors binding compartments Muhammad et al, 2018). The PDB files of the best docked conformation were generated using Accerlrys discovery studio and were introduced into Chimera 1.1v to generate and view the hydrophobic and hydrophilic interactions.…”
Section: In Silico Studiesmentioning
confidence: 99%